2013
DOI: 10.1111/eip.12027
|View full text |Cite
|
Sign up to set email alerts
|

Long‐acting injectable antipsychotics in early psychosis: a literature review

Abstract: The available evidence does suggest that long-acting injectable antipsychotics can be used safely and effectively in early stages of the illness, and that they may be associated with better outcomes than with oral medications. However, this is largely supported by evidence from naturalistic cohort studies and a small number of controlled trials of risperidone long-acting injection. Evidence for olanzapine and paliperidone long-acting injectables in particular is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 49 publications
(83 reference statements)
2
51
0
Order By: Relevance
“…This is important as dysregulation of the normal myelination trajectory may contribute to the functional deterioration and treatment resistance observed in chronic schizophrenia [139]. The clinical imperative to reduce relapse rates stems also from the added economic burden of treating relapse, possibly leading to unavoidable hospital admissions [134,[141][142][143][144][145][146][147]. Finally, relapses due to medication non-adherence can have devastating social consequences themselves.…”
Section: Results Of Descriptivementioning
confidence: 99%
“…This is important as dysregulation of the normal myelination trajectory may contribute to the functional deterioration and treatment resistance observed in chronic schizophrenia [139]. The clinical imperative to reduce relapse rates stems also from the added economic burden of treating relapse, possibly leading to unavoidable hospital admissions [134,[141][142][143][144][145][146][147]. Finally, relapses due to medication non-adherence can have devastating social consequences themselves.…”
Section: Results Of Descriptivementioning
confidence: 99%
“…However, this practice is not evidence based and there are anecdotal reports that LAIs may be of particular value when used early in the course of illness 16, 23, 26, 27, 28, 29, 30. Recently, a few randomized studies have demonstrated the value of using APs early in the course of schizophrenia 31, 32.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, given the importance of continuous treatment in the early phases of schizophrenia, LAI APs may also be a treatment option [Kim et al 2012;Emsley et al 2013], and in the context of a shared decision-making approach Kirschner et al 2013], it could reduce the negative image and stigmatization attached to depots [Kirschner et al 2013].…”
Section: Guidelines and Recommendations For The Treatment Of Schizophmentioning
confidence: 99%